The evolution of seed dormancy: environmental cues, evolutionary hubs, and diversification of the seed plants. Issue 1 (28th March 2014) - Willis, Charles G.; Baskin, Carol C.; Baskin, Jerry M.; Auld, Josh R.; Venable, D. Lawrence; Cavender‐Bares, Jeannine; Donohue, Kathleen; Rubio de Casas, Rafael; The NESCent Germination Working Group
Summary Seed dormancy, by controlling the timing of germination, can strongly affect plant survival. The kind of seed dormancy, therefore, can influence both population and species‐level processes such as colonization, adaptation, speciation, and extinction. We used a dataset comprising over 14 000 taxa in 318 families across the seed plants to test hypotheses on the evolution of different kinds of seed dormancy and their association with lineage diversification. We found morphophysiological dormancy to be the most likely ancestral state of seed plants, suggesting that physiologically regulated dormancy in response to environmental cues was present at the origin of seed plants. Additionally, we found that physiological dormancy (PD), once disassociated from morphological dormancy, acted as an 'evolutionary hub' from which other dormancy classes evolved, and that it was associated with higher rates of lineage diversification via higher speciation rates. The environmental sensitivity provided by dormancy in general, and by PD in particular, appears to be a key trait in the diversification of seed plants.